Opportunities and Challenges for Bank Syariah Indonesia in Increasing Syariah KPR Financing Distribution - Astutik, Wahyuni Sri; Limantara, Arthur Daniel (LPPM of NAROTAMA UNIVERSITY, 2024)
The Objective of the study is to know what challenges and opportunities for Bank Syariah Indonesia (BSI) in distributing Syariah housing funds (KPR) are. It was done by the analysis and diagnosis of the company’s environment. The research uses a literature research technique by collecting data with documentation, notes, books, and articles. Whilst checklist classification material study was used for data collection instruments. The data analysis techniques used are by gathering the essence of focused study through collected sources and then analyzed the data to determine the connections. The results show that BSI has a promising opportunity to obtain profit in the distribution of syariah credit financing housing scheme with a stimulus provided by the government. Moreover, the economy is starting to be conducive which implicates social support conditions, optimalization in utilization-tool technology, and lastly the company’s good image. As for BSI’s challenges, it is necessary to enhancement literacy of syariah finance and intensive education finance especially to the consumers and to society in order get to know BSI more.